2017
DOI: 10.1038/s41598-017-03453-x
|View full text |Cite
|
Sign up to set email alerts
|

On the impact of Vertical Alignment of MoS2 for Efficient Lithium Storage

Abstract: Herein, we report energy storage devices, which are based on densely packed, vertically aligned MoS2 (VA-MoS2) or planar oriented MoS2 (PO-MoS2) and compare their electrochemical performances. The VA-MoS2 films have been processed by chemical vapor deposition (CVD) to reach unprecedented micron-scale thick films while maintaining the vertical alignment for the whole thickness. The VA-MoS2 and the PO-MoS2 films form a high-performance Li-ion electrode, reaching the theoretical limits of reversible capacity for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
38
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 48 publications
(41 citation statements)
references
References 52 publications
(49 reference statements)
3
38
0
Order By: Relevance
“…Atomic‐thin semiconductors, such as the transition metal dichalchogenide (TMDC) family have attracted great scientific, and technological attention due to their interesting physical and chemical properties, which make them promising candidates in a wide range of applications, such as nanoeletcronics, [ 7 ] optoelectronics, [ 8 ] catalysis, [ 9 ] and energy storage. [ 9c–e,10 ] Such atomic crystals were also suggested as solid electrolytes in resistive switching devices. [ 1a,11 ] To our knowledge, only planar single‐ and few‐layer 2D materials were implemented into memristor devices with top and bottom metal contacts.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Atomic‐thin semiconductors, such as the transition metal dichalchogenide (TMDC) family have attracted great scientific, and technological attention due to their interesting physical and chemical properties, which make them promising candidates in a wide range of applications, such as nanoeletcronics, [ 7 ] optoelectronics, [ 8 ] catalysis, [ 9 ] and energy storage. [ 9c–e,10 ] Such atomic crystals were also suggested as solid electrolytes in resistive switching devices. [ 1a,11 ] To our knowledge, only planar single‐ and few‐layer 2D materials were implemented into memristor devices with top and bottom metal contacts.…”
Section: Introductionmentioning
confidence: 99%
“…Vertically aligned (VA) TMDCs were shown to be formed by the calchogenization of transition metal thin films or foils. [ 9a,13 ] Thin films of VA‐MoS 2 , [ 9a,10,13a,b ] ‐MoSe 2 , [ 13b ] and ‐WSe 2 [ 13c ] were reported and their electronic and catalytic properties tested. These films therefore, offer some interesting features, not available on planar few‐layer TMDCs.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Li found that larger, dense exposed edges of vertical MoS 2 sheets can lead to a more active HER electro-catalyst [ 15 ]. However, while extensive studies have been devoted to two-dimensional materials which lie flat on the substrates [ 18 , 19 , 20 , 21 ], few reports have been developed regarding the growth of vertically standing MoS 2 nanosheets [ 6 , 11 , 22 , 23 , 24 , 25 , 26 ]. The growth of such vertically standing nanosheets is still challengeable, and more efforts should be made to explore the growth characteristics of nanosheets.…”
Section: Introductionmentioning
confidence: 99%
“…4(c) and 4(d), EBI-treated MoS 2 grew uniformly with exposed edge sites. Since these vertically exposed edge sites of MoS 2 play an important role in improving catalytic activity and sensing property [16], we expected EBI-treated MoS 2 to be a potential candidate for gas sensor and hydrogen evolution reaction (HER). Furthermore, because morphology of MoS 2 is significantly affected by fabrication parameters [14,15], optimized sputtering and EBI parameters for more dense and uniform morphology would be required to application of EBI-treated MoS 2 in gas sensor and HER.…”
Section: Resultsmentioning
confidence: 99%